ASUHAN KEBIDANAN PADA IBU NIFAS NY “D”P3A0H3 DIRUMAH BERSALIN BUNDA PUJA - Zuleha, Zuleha; Harianis, Sandra (STIKES HUSADA GEMILANG, 2022)
The postpartum begins after the birth of the placenta and ends when the uterus organs return to their pre-pregnancy state. The postpartum lasts about 6 weeks. It is estimated that 60% of maternal deaths due to pregnancy occur after childbirth and 50% of postpartum deaths occur within the first 24 hours, one of the causes is puerperal bleeding because it requires proper treatment. The purpose of this midwifery care is to be able to provide comprehensive midwifery care services to the post-partum Mrs.